Studies on application of fish waste for synthesis of high quality biodiesel - Madhu D.; Singh B.; Sharma Y.C. (My University, 2025)
A low cost raw material obtained from the discarded parts of fish (Cirrhinus mrigala, Cirrhinus cirrhosa, Cirrhinus reba) was utilized as feedstock oil and catalyst for the synthesis of biodiesel. Esterification followed by transesterification was carried out for the synthesis of biodiesel from waste fish oil. The discarded parts of fish after extraction of oil that included fins, tails and bones were used to derive a low cost heterogeneous catalyst for the synthesis of biodiesel. The catalyst characterized by thermo-gravimetric analysis and X-ray diffraction analysis showed the calcination temperature required and the phase of the catalyst respectively. The HAP (hydroxyapatite) present in the waste parts of fish was converted into β-tri-calcium phosphate when calcined at 900 °C for 2 h. The catalyst, β-tri-calcium phosphate was studied for its morphology and porous structure by scanning electron microscopy. A moderate experimental condition (1 : 6.5 molar ratio of oil : methanol, 1.5 wt% of heterogeneous catalyst with respect to oil) was taken for synthesis of biodiesel from waste fish oil. Biodiesel characterized by proton NMR showed a high conversion of waste fish oil to biodiesel (i.e. >96%). The yield of biodiesel determined by gravimetric method was >95%. The heterogeneous catalyst, β-tri-calcium phosphate was reused up to five times without significant loss in its activity. This journal is © the Partner Organisations 2014.